A Case of Chronic Ectopic Pregnancy Manifested by Rectal Bleeding - Nina Vukas Radulovic; Maria Bullarbo; Erling Ekerhovd (Case Reports in Obstetrics and Gynecology)
Ectopic pregnancy resulting in perforation of the rectum and rectal bleeding is clinically rare. We report an extremely rare case of chronic ectopic pregnancy with decreasing low levels of serum β-HCG resulting in rectal bleeding. A 31-year-old woman, gravida 3, para 3, with moderate abdominal pain and rectal bleeding was diagnosed with a tubal pregnancy. The tube was adherent to the rectum. Following salpingo-oophorectomy, the perforation of the rectum was sutured. Biopsies from the rectum as well as the tube confirmed chronic ectopic pregnancy. This case illustrates that diagnosing ectopic pregnancy is sometimes extremely challenging and it underlines the importance of follow-up consultations when the final diagnosis has not yet been reached.